Pharmacy and Social Media : A Bioethical Perspective - Beitia-Berrotarán, Guadalupe (2024)
Social media has rapidly expanded to fulfill various purposes, such as keeping groups of people connected, sharing personal or organizational knowledge, and promoting commercial products. Pharmacies have not been left out of this trend, with many now using platforms like WhatsApp, Instagram, X (formerly Twitter), and others. The use of social media in healthcare can offer significant benefits in promoting and improving health, provided it is used responsibly. However, if misused, it carries substantial risks that can negatively impact public health and harm the credibility of both individual professionals and the profession as a whole. Therefore, before a pharmacist engages with social media, it is important to carefully consider the potential risks and benefits. This reflection should focus on ensuring actions that promote humanized healthcare and patient care, paying special attention to three key principles: safeguarding privacy and confidentiality, maintaining truth and accuracy, and upholding both personal and professional responsibility. When it comes to professional responsibility, it is crucial to remember the commitment to the broader professional community. Any sensationalism or misinformation spread by a pharmacist online can have a damaging impact on the reputation of the entire pharmacy profession.